Risk calculator for predicting postoperative pneumonia after gastroenterological surgery based on a national Japanese database. Issue 4 (22nd April 2019) - Takesue, Yoshio; Miyata, Hiroaki; Gotoh, Mitsukazu; Wakabayashi, Go; Konno, Hiroyuki; Mori, Masaki; Kumamaru, Hiraku; Ueda, Takashi; Nakajima, Kazuhiko; Uchino, Motoi; Seto, Yasuyuki
Abstract: Background: The aim of the present study was to develop a risk calculator predictive of postoperative pneumonia in patients undergoing gastroenterological surgery. Methods: We analyzed data from 382 124 patients undergoing eight main gastroenterological surgeries between 2011 and 2013 using the National Clinical Database in Japan. A risk model was developed using multivariate logistic regression analysis with patient data from 2011 to 2012 (n = 247 604) and validated using data from 2013 (n = 134 520). Results: Pneumonia was observed in 11 105 patients (2.9%). After the input of significant primary disease and surgical procedures, 18 patient characteristics including gender, chronic obstructive pulmonary disease, sepsis, and need for any assistance in the activities of daily living, six laboratory parameters, and two intraoperative factors were used for risk calculation. Area under the receiver‐operating characteristic curve was 0.822 (95% confidence interval, 0.817‐0.826) in the derivation group and 0.826 (0.819‐0.832) in the validation group. Conclusion: The risk calculator accurately predicted the occurrence of pneumonia following gastroenterological surgery. Abstract : A risk calculator predictive of postoperative pneumonia was developed from the data of 382 124 patients undergoing eight main gastroenterological surgeries using the National Clinical Database in Japan. βi is the coefficient of the variable Xi in the logistic regression equation.